Library mesenger, April - June 2012 (Confluenţe Bibliologice, 2012)
This article reflects the most significant activities carried out within the USARB Scientific Library in April - June 2019.
Keywords: bibliographic presentation; continuing professional training; cultural activities; editorial activity